The Arabidopsis LYST INTERACTING PROTEIN 5 Acts in Regulating Abscisic Acid Signaling and Drought Response - Xia, Zongliang; Huo, Yongjin; Wei, Yangyang; Chen, Qiansi; Xu, Ziwei; Zhang, Wei (Frontiers in Plant Science, 2016)
Multivesicular bodies (MVBs) are unique endosomes containing vesicles in the lumens and play essential roles in many eukaryotic cellular processes. The Arabidopsis lyst interacting protein 5 (LIP5), a positive regulator of MVB biogenesis, has critical roles in biotic and abiotic stress responses. However, whether the ABA signaling is involved in LIP5-mediated stress response is largely unknown. Here, we report that LIP5 functions in regulating ABA signaling and drought response in Arabidopsis. Analyses of a LIP5 promoter-β-glucuronidase (GUS) construct revealed substantial GUS activity in whole seedlings. The expression of LIP5 was induced by ABA and drought, and overexpression of LIP5 led to ABA hypersensitivity, enhanced stomatal closure, reduced water loss, and, therefore, increased drought tolerance. On the contrary, LIP5 knockdown mutants showed ABA-insensitive phenotypes and reduced drought tolerance; suggesting that LIP5 acts in regulating ABA response. Further analysis using a fluorescent dye revealed that ABA and water stress induced cell endocytosis or vesicle trafficking in a largely LIP5-dependent manner. Furthermore, expression of several drought- or ABA-inducible marker genes was significantly down-regulated in the lip5 mutant seedlings. Collectively, our data suggest that LIP5 positively regulates drought tolerance through ABA-mediated cell signaling.